2011
DOI: 10.1111/j.1476-5381.2011.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil analgesia in experimental arthritis involves suppression of intra‐articular TNF release

Abstract: BACKGROUND AND PURPOSEWe investigated the effect of the phosphodiesterase-5 inhibitor, tadalafil, on the acute hypernociception in rat models of arthritis. EXPERIMENTAL APPROACHRats were treated with either an intra-articular injection of zymosan (1 mg) or surgical transection of the anterior cruciate ligament (as an osteoarthritis model). Controls received saline intra-articular or sham operation respectively. Joint pain was evaluated using the articular incapacitation test measured over 6 h following zymosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Rats do not express IL-8 but an ortholog cytokine, CINC-1, instead, which plays a major role in cell recruitment during inflammation [18]. Different from what was observed with TNFa and IL-1b, SR did not alter joint levels of CINC-1 in zymosan arthritis.…”
Section: Discussionmentioning
confidence: 49%
“…Rats do not express IL-8 but an ortholog cytokine, CINC-1, instead, which plays a major role in cell recruitment during inflammation [18]. Different from what was observed with TNFa and IL-1b, SR did not alter joint levels of CINC-1 in zymosan arthritis.…”
Section: Discussionmentioning
confidence: 49%
“…This reveals that in the functional up-or down-regulation of nociceptors, cGMP plays an important role (Duarte et al 1990). Additionally, in the modulation of pain perception (Jain and Kulkarni 1999;Pavone et al 1997;Tao et al 2000) and in nociception in arthritis (Rocha et al 2011) the involvement of NO-cGMP pathway has been suggested by various researchers.…”
Section: Introductionmentioning
confidence: 93%
“…Of the various PDEs, PDE-5, -6, and -9 are specific to cGMP; however, PDE5 is most relevant to cGMP inactivation inside cells (Rocha et al 2011). PDE5 inhibitors are known to be effective via NO-cGMP pathway (Chen et al 2012) and potentiate the effect of endogenously released NO by slowing the degradation of cGMP (Demchenko et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to our study, another study showed that the PDE 5 inhibitor sildenafil enhanced diclofenac anti-nociceptive effects in formalin tests [18]. Furthermore, one study demonstrated that the PDE 5 inhibitor tadalafil has analgesic effects on experimental arthritis by suppressing TNF alpha release in joints [19]. In contrast to these studies, it has been suggested that zaprinast, another PDE 5 inhibitor, has no effect on hyperalgesia induced by prostaglandin E2 [20].…”
Section: Discussionmentioning
confidence: 40%